Cover Image. Issue 11 (24th October 2017) - Sîrbulescu, Ruxandra F.; Ilieş, Iulian; Meyer, Annette; Zupanc, Günther K.H.
Abstract : Cover: The cover, by Ruxandra F. Sîrbulescu et al., is based on the Research Article Additive neurogenesis supported by multiple stem cell populations mediates adult spinal cord development: A spatiotemporal statistical mapping analysis in a teleost model of indeterminate growth, DOI:10.1002/dneu.22511 .